2021
DOI: 10.1161/strokeaha.120.031961
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Informant Questionnaire on Cognitive Decline in the Elderly for Detecting Preexisting Dementia in Transient Ischemic Attack and Stroke

Abstract: Background and Purpose: Prestroke dementia prevalence is high and impacts outcome. Although the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) is being used to assess prestroke cognition, data on its validity for prestroke dementia are lacking. We studied the accuracy of the short-form (16-item) IQCODE for pre-event dementia in a population-based study of all transient ischemic attack (TIA)/stroke. Methods: All patients with TIA/st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…Our findings are consistent with those of Nieuwkerk et al 21 who found an IQCODE-SF AUROC of 0.94 for pre-stroke dementia assessment. Similarly, IQCODE-SF scores have previously been associated with periventricular WMH, medial temporal atrophy, and global atrophy in an atrial fibrillation population.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are consistent with those of Nieuwkerk et al 21 who found an IQCODE-SF AUROC of 0.94 for pre-stroke dementia assessment. Similarly, IQCODE-SF scores have previously been associated with periventricular WMH, medial temporal atrophy, and global atrophy in an atrial fibrillation population.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those of Nieuwkerk et al 21 . who found an IQCODE‐SF AUROC of 0.94 for pre‐stroke dementia assessment.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations